(untitled) (Communication & Society, 2021)
In the last few years, affect has entered the field of politics through both the media and political actors themselves. This article is based on the hypothesis that the images of affect that illustrate contemporary political narratives in the media reflect different visual motifs which are linked to an iconographic tradition that began in the art world. Through the iconographic analysis of images published in the three newspapers in Spain with the largest general readership (El País, El Mundo, and La Vanguardia) from 2011 to 2017, this article identifies three visual motifs of affect: the handshake, the hug, and the kiss. The study of these motifs highlights the survival of certain forms of emotion that are easily recognisable and engage with a longstanding iconographic tradition. At the same time, the article inquiries into the meanings derived from these iconographies and their implications on the representation of politics and of political leaders. The proliferation of motifs of affect in politics then connects with both the mediatisation of politics and an affective turn, which invites us to re-examine the role of emotion in the contemporary public sphere.